Bunker procurement strategies of liner companies part III : environmental regulations - Mo, Anthony Chaoyuan. (2011)
The bunker procurement strategy of a liner shipping company can determine the long term survival of the firm in the global market due to the volatile bunker prices. Part III of the project relates to the environmental regulations in particular the MARPOL Annex VI and EC Sulphur Directive which affects global and short sea liner companies. The requirements of the regulation are mandatory and stringent. Vessels that operate within the specific zones will be impacted in the financial and technical sense as they burn low sulphur fuel oil. This report explores both impacts. It is important to examine the impacts and execute differing strategies such as slow steaming to reduce the need for bunker procurement, enhancing supplier relationships to ensure product quality and assurance, and the exploration of abatement technologies. This will allow liner companies of today to better understand the areas of trade and if there is a need to alter their current procurement strategies in the short to long term. The strategic long term perspective should be upheld by them. The bunker procurement strategies that allow for the best cost control will enable liner shipping companies to compete both efficiently and effectively to boost profits.